Bidens pilosa L: efeitos protetores na inflamação intestinal - Quaglio, Ana Elisa Valencise [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Inflammatory Bowel Disease (IBD) comprises basically two distinct diseases: Crohn's disease (CD) and Ulcerative Colitis (UC), both characterized by chronic inflammation of the intestine, with exacerbation periods followed by long intervals of remission of symptoms. Despite being subject of research for decades, its etiology is still unknown and a single agent or isolated mechanism is not enough to produce or trigger the disease. The difficulty in effectively treat all patients based on the poor response to drug and in the several side effects that the treatments presents, supports the search for new sources of compounds useful in the treatment and prevention of IBD. Among the various strategies available, the research of medicinal plants shows promise. Bidens pilosa L., Asteraceae, is a weed with wide distribution and occurrence in some countries and is known in Brazil as picão-preto. Although it is considered a weed without economic importance, has been used in various populations with medical purpose and its application in various diseases may be due to its chemical composition rich in phytol and polyunsaturated fatty acid (palmitic acid, oleic acid and linoleic acid) compounds known to have anti-inflammatory and/or antioxidants effects. In the present study the supercritical extract of Bidens pilosa L. was able to reduce the levels of pro-inflammatory mediators, such as MPO, IL-1β and TNF-α associated with modulation of anti-inflammatory factors such as IL-10, both in the preventive and curative protocols. Also modulates gene expression of genes related to inflammation and mucosal protection, such as HSP70 and MUC. In addition to the biochemical changes might notice a histological improvement in colonic samples analyzed by electron microscopy. Together with structural changes was an increase in the production and secretion of mucin, mucosal protective agents. Thereby, B.pilosa extract is an important source of compounds which may ...

A Doença Inflamatória Intestinal (DII) engloba, fundamentalmente, duas doenças distintas: a Doença de Crohn (DC) e a Colite Ulcerativa (CU), ambas caracterizadas por uma inflamação crônica do intestino, com períodos de exacerbação seguidos de intervalos prolongados de remissão dos sintomas. Apesar da DII ser objeto de pesquisa há várias décadas, a sua etiologia ainda é desconhecida e um único agente ou mecanismo isolado não parecem ser suficientes para produzir ou desencadear a doença. A dificuldade em se tratar de forma efetiva todos os pacientes com DII em função da baixa resposta aos fármacos associada a diversos efeitos colaterais corrobora a busca de novas fontes de compostos úteis no tratamento e prevenção da DII. Entre as várias estratégias disponíveis, a pesquisa de plantas medicinais se mostra promissora. Bidens pilosa L., família Asteraceae, é uma erva daninha com ampla distribuição e ocorrência em diversos países, sendo conhecida no Brasil como picão-preto. Apesar de ser considerada uma erva daninha sem importância econômica tem sido utilizada em várias populações com finalidade medicinal e sua aplicação em diversas enfermidades pode ser devido a sua composição química rica em phytol e ácido graxos poli-insaturados (ácido palmítico, ácido oleico ácido linoleico), compostos com efeitos anti-inflamatórios e/ou antioxidantes. No presente trabalho o extrato supercrítico de Bidens pilosa L. foi capaz de reduzir os níveis de mediadores pró-inflamatórios, como MPO, IL-1β e TNF-α além de modular fatores anti-inflamatórios como IL-10 tanto no protocolo preventivo quanto no curativo. Modulou também a expressão gênica de genes relacionados à inflamação e proteção da mucosa, como HSP70 e MUC. Além das alterações bioquímicas pôde-se notar uma melhora histológica em amostras de cólon analisadas por microscopia eletrônica. Associada a alterações estruturais ocorreu um ...
Keywords: Doenças inflamatórias intestinais; Erva daninha; Bidens pilosa - Uso terapêutico; Extratos vegetais; Intestines - Diseases; Bidens pilosa